Biosynthesis and Potential Applications of Silver and Gold Nanoparticles and Their Chitosan-Based Nanocomposites in Nanomedicine. (19th November 2018) - Katas, Haliza; Moden, Noor Zianah; Lim, Chei Sin; Celesistinus, Terence; Chan, Jie Yee; Ganasan, Pavitra; Suleman Ismail Abdalla, Sundos
Abstract : Biosynthesized or biogenic metallic nanoparticles, particularly silver and gold nanoparticles (AgNPs and AuNPs, respectively), have been increasingly used because of their advantages, including high stability and loading capacity; moreover, these nanoparticles are synthesized using a green and cost-effective method. Previous studies have investigated reducing and/or stabilizing agents from various biological sources, including plants, microorganisms, and marine-derived products, using either a one-pot or a multistep process at different conditions. In addition, extensive studies have been performed to determine the biological or pharmacological effects of these nanoparticles, such as antimicrobial, antitumor, anti-inflammatory, and antioxidant effects. In the recent years, chitosan, a natural cationic polysaccharide, has been increasingly investigated as a reducing and/or stabilizing agent in the synthesis of biogenic metallic nanoparticles with potential applications in nanomedicine. Here, we have reviewed the mechanism of biosynthesis and potential applications of AgNPs and AuNPs and their chitosan-mediated nanocomposites in nanomedicine.